Investigating the Algodones Dune Field of Southern California II : Using Geospatial Techniques - Galloway, Madison; Hanson, Paige; Mangin, Matthew; Rickey, Brittany; Walker, Whitney; Goettl, Martin; Jol, Harry M. (My University, 2019)
The Eastern Algodones Dunes, located in the Sonoran Desert, Imperial county, Southern California, stretch 72 kilometers and are 9.7 kilometers in width. The dunes were hypothesized to be a result of sediment blown from ancient Lake Cahuilla and are characterized by distinct regions: Glamis Beach, Gordon's Well, Buttercup, Midway, and Patton's Valley. The purpose of the research was to create a digital elevation model (DEM) of the sand starved dune complex by collecting aerial imagery using a DJI Phantom-4PG UAV. To improve overlap and tie points, the aerial imagery has a 75% front lap and a 65% side lap. The flight was flown at 50 meters above ground level and took 20 swaths overhead. To enhance the accuracy of the DEM, ten ground control points (GCPs) were collected using a REACH RS+ RTK GNSS receiver. In addition, a topographic survey was conducted using a TopCon laser leveler to more accurately geometrically correct the collected ground penetrating radar transects.
Color poster with text, images, and photographs
Keywords: Ground control points (GCP); Geospatial data; Geology; Posters